Boosting Children's Persistence through Scientific Storybook Reading. Issue 2 (15th March 2022) - Haber, Amanda S.; Kumar, Sona C.; Corriveau, Kathleen H.
ABSTRACT: Eighty-six 4- and 5-year-old children were assigned to one of four conditions, three experimental conditions, in which children read a story about a famous scientist, and one baseline condition. In the Achievement condition: the scientist was described as receiving awards and recognition through their lifetime, with no discussion of setbacks; in the Intellectual Struggles, the scientist was described as making mistakes along the way to success; and in the Life Struggles, the book emphasized personal struggles, such as having no money for food. In the Baseline condition, children completed a persistence task without having first read the story. In each experimental condition, children were asked 12 questions adapted from the Dimension of Mastery Questionnaire-18, which examined their persistence and motivation when faced with a challenging task. Finally, children were presented with the persistence task. Analyses revealed that children in the Intellectual Struggles and Life Struggles conditions persisted longer on the task than children in the Achievement Condition . These findings suggest that storybooks that emphasize the process of science, rather than solely focusing on achievement can impact persistence as well as feelings of relatedness in STEM.